Komunikasi Terapeutik Psikolog dalam Menangani Klien Pengidap Deliberate Self-Harm - Galuh Valencia; Purwanti Hadisiwi; Ditha Prasanti (Jurnal Spektrum Komunikasi, 2021)
This study aims to find out psychologist therapeutic communication in dealing with deliberate self-harm clients in 3 research question. This study uses a phenomenological approach. In collecting data, researchers used an interview technique with five informants who were psychologists that practiced and domiciled in Bandung. The results of this study indicate the meaning of a DSH client for a psychologist into three meanings, those who have irrational thoughts, people that have fragile emotion, and those whose emotions are hidden or looking for attention. The experience of psychologist therapeutic communication in dealing with DSH clients is found in 4 major themes: techniques for building therapeutic relationships with clients, the key to understanding clients: active listening, being careful with non- verbal messages, feedback: reserved question. The psychologist's way of handling DSH clients is by handling it like a tailormade (adjusted to the personality and problems of the clients)